Village Funds in the Rural Credit Market of Thailand - Lukas Menkhoff; Ornsiri Rungruxsirivorn (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2009)
This paper examines the contribution of recently introduced village funds in rural Thailand, one of the largest microfinance programs ever implemented. We use a cross-sectional approach examining village funds in relation to competing financial institutions. We find, first, that village funds reach the target groups of lower income households better than existing institutions from the formal sector. Second, village funds provide loans to those kinds of borrowers which tend to be customers of informal financial institutions. Third, village funds help to reduce credit constraints. Overall, village funds seem to provide services in the intended direction.
Keywords: O16; O17; G21; 330; informal financial institutions; microfinance; credit constraint